2021
DOI: 10.1136/rmdopen-2021-001594
|View full text |Cite
|
Sign up to set email alerts
|

Point of view on the vaccination against COVID-19 in patients with autoimmune inflammatory rheumatic diseases

Abstract: In view of the COVID-19 pandemic, there is an unmet clinical need for the guidelines on vaccination of patients with autoimmune inflammatory rheumatic diseases (AIIRD). This position paper summarises the current data on COVID-19 infection in patients with AIIRD and development of vaccines against COVID-19, discusses the aspects of efficacy and safety of vaccination, and proposes preliminary considerations on vaccination against COVID-19 in patients with AIIRD, mainly based on the expert opinion and knowledge o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 78 publications
1
56
0
3
Order By: Relevance
“…In a study of 261 patients with cancer, Thakkar et al showed the signi cantly lower seroconversion observed in patients with hematological malignancy after Covid-19 infection, particularly in patients exposed to anti-CD20 antibody containing therapy [5]. B-cell depletion by treatment with rituximab or obinutuzumab can also cause suppression of the immune response to vaccines [6][7][8][9][10][11]. These monoclonal antibodies act against the surface antigen protein CD20 expressed on B-lymphocyte during most of its developmental stages [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of 261 patients with cancer, Thakkar et al showed the signi cantly lower seroconversion observed in patients with hematological malignancy after Covid-19 infection, particularly in patients exposed to anti-CD20 antibody containing therapy [5]. B-cell depletion by treatment with rituximab or obinutuzumab can also cause suppression of the immune response to vaccines [6][7][8][9][10][11]. These monoclonal antibodies act against the surface antigen protein CD20 expressed on B-lymphocyte during most of its developmental stages [12].…”
Section: Introductionmentioning
confidence: 99%
“…Another study found that In uenza vaccine responsiveness was poor in patients on rituximab [8]. In light of such results, several groups advise patients to consider the timing of Covid-19 vaccination relative to their anti-CD20 antibody therapy schedule [9][10][11]. Detection of regional lymphadenopathy after Covid-19 vaccines on various imaging modalities has been reported in case reports and small cohorts [13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive data about the impact of anti-SARS-CoV-2 vaccines in patients with immunemediated disorders are eagerly awaited, since people living with these diseases were excluded from registration trials, [2][3][4] despite constituting a risk group for severe SARS-CoV-2-realated disease (COVID-19) [5][6][7] and, potentially, for adverse immune-mediated post-vaccinal events. [8][9][10][11] To contribute in filling this knowledge gap, we studied 55 consecutive patients (54 health professionals) with rheumatic diseases and primary immunodeficiencies, for a median (IQR) of 66 (42-75) days from the first and 45 (20-52) days from the second dose of the BNT162b2 vaccine 2 (detailed methods: online supplemental material 1). Thirty-eight patients (69%) had one or more comorbidities, including allergy in 22 cases (table 1).…”
mentioning
confidence: 99%
“…At time of vaccination, 42/55 patients had been in remission for 20 months. The median disease duration was 11 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) years. Fifty-one patients (93%) were taking one or more immunosuppressive/immunomodulating drugs beside other treatments (online supplemental tables 1 and 2).…”
mentioning
confidence: 99%
“…Because efficacy of the vaccine is unclear both in overly immunosuppressed patients and in those with disordered immune activity, patients with RDs should continue high vigilance in social distancing, wearing masks and avoiding unnecessary contact with other individuals [31]. Still there is an unmet clinical need for the guidelines on vaccination of AIIRD patients [32].…”
Section: Discussionmentioning
confidence: 99%